"You" - Lim, Hui Yi (Nanyang Technological University, 2023)
“YOU” is a pixel RPG game built in Unity. The player plays as BOB, who has just moved to a new town. The game mimics a life simulator and is inspired by vintage pixel games. The player gets to interact with NPCs and objects in the game world, as well as perform tasks and earn in-game currency. As the game progresses, it gradually becomes more unhinged and chaotic. It explores the concepts of playing god and breaking the fourth wall and carries an increasingly sarcastic and cynical tone. BOB passes his judgment of the player’s choices and confronts the player directly at the end of the game.